2x - 6y = 12
so we pick any number for x and then solve for y
lets say x = 0
2(0) - 6y = 12
-6y = 12
y = -12/6
y = -2....so when x = 0, y = -2....(0,-2) <== one point
lets say x = 1
2(1) - 6x = 12
2 - 6x = 12
-6x = 12 - 2
-6x = 10
x = -10/6
x = - 5/3...so when x = 1, y = -5/3....(1,-5/3) <== another point
Lets say x = 2
2(2) - 6y = 12
4 - 6y = 12
-6y = 12 - 4
-6y = 8
y = -8/6
y = - 4/3....so when x = 2, y = -4/3.....(2,-4/3) <== another point
lets say x = 3
2(3) - 6y = 12
6 - 6y = 12
-6y = 12 - 6
-6y = 6
y = -6/6
y = -1....so when x = 3, y = -1.....(3,-1) <== another point
now there is 4 points.
Answer:
option A, option C, option D
Step-by-step explanation:
a) 1 ÷ m/6
can be written as
÷ 
b) sides in (m/6) will change if both has to multiply
c) 1 ÷ m/6
can be written as
1 * 6/m
1(
) and wont make change to answer. so matches with the question.
d)
1 ÷ m/6
1 * 6/m
1 * 6 * 
6 * 
6 ÷ m ..therefore true
e)
1 ÷ m/6
1 * 6/m
6/m ....does not match or can be converted to the following so wrong
- Therefore A, C, D are correct and B and E is wrong.
1) 135 2) 119.40 if you still need the rest reply back to this answer
triangle B. because congruent is supposed to be the same shape same size but triangle b is same shape but a different size